2011
DOI: 10.1016/j.ajem.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tricyclic antidepressant-like complications after cyclobenzaprine overdose

Abstract: Background: The cyclobenzaprine structure is similar to amitriptyline; however, tricyclic antidepressant (TCA)-like wide complex dysrhythmia has not been reported. Our objective was to determine the incidence of TCA-like effects in cyclobenzaprine overdoses as reported to 6 poison centers for 2 years. We compared the incidence of these effects to amitriptyline overdoses collected during the same period. Methods: We performed a retrospective review of 2 years of cases as reported to the Texas Poison Center Netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Other medications such as antiarrhythmics [ 36 38 ], non-TCA antidepressants [ 39 , 40 ], antiepileptic medications [ 41 43 ], cyclobenzaprine [ 43 , 44 ], propranolol [ 45 ], cocaine [ 46 ], and certain antihistamines [ 47 ] may produce similar ECG and clinical manifestations with favorable response to similarly administered IV sodium bicarbonate. Amantadine overdose may result in a similar cardiac sodium channel toxicity though IV sodium bicarbonate was not specifically used in the reported cases because of concomitant hypokalemia [ 48 ].…”
Section: The Role Of Sodium Bicarbonate In the Management Of Sodiumentioning
confidence: 99%
“…Other medications such as antiarrhythmics [ 36 38 ], non-TCA antidepressants [ 39 , 40 ], antiepileptic medications [ 41 43 ], cyclobenzaprine [ 43 , 44 ], propranolol [ 45 ], cocaine [ 46 ], and certain antihistamines [ 47 ] may produce similar ECG and clinical manifestations with favorable response to similarly administered IV sodium bicarbonate. Amantadine overdose may result in a similar cardiac sodium channel toxicity though IV sodium bicarbonate was not specifically used in the reported cases because of concomitant hypokalemia [ 48 ].…”
Section: The Role Of Sodium Bicarbonate In the Management Of Sodiumentioning
confidence: 99%
“…Previous case reports have documented the use of sodium bicarbonate therapy in cyclobenzaprine toxicity (Bebarta et al, 2011). This may theoretically benefit patients, especially those with widened QRS complexes due to structural similarity to tricyclic antidepressants.…”
Section: Management Of Cyclobenzaprine Toxicitymentioning
confidence: 97%
“…Clinical manifestations following an acute toxic ingestion may be consistent with anticholinergic toxicity (Bebarta et al, 2011). While it has been suggested that QRS complex widening, ventricular dysrhythmias, and seizures may occur due to its structural similarity to tricyclic antidepressants, several previous studies have demonstrated that the actual incidence of these events in the setting of cyclobenzaprine toxicity is relatively rare (Spiller et al, 1995;Bebarta et al, 2011).…”
Section: Management Of Cyclobenzaprine Toxicitymentioning
confidence: 98%
“…48 A meta-analysis from 15 randomized controlled trials (RCTs) with a total of 3779 patients found a greater incidence of tachycardia (9%) in the paliperidone group with an attributable risk of 4. 55 Amitriptyline intoxication was also associated with tachycardia, 56,57 and more than 60% of these individuals experienced increased heart rate. 52 It is contraindicated for treatment of psychotic symptoms in older adults with dementia due to its strong association with stroke during treatments.…”
Section: Chronotropic Effectsmentioning
confidence: 99%